THE ROLE OF MEDICOLEGAL ETHICS IN CASES OF SEXUALABUSE OF CHILDREN BY STEPFATHERS - Nurul Ummi Rofiah; Anggraeni Endah Kusumaningrum (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
As the nation's next generation, children should be cared for and protected so that their future can be guaranteed and can achieve their goals. Childhood or adolescence who should still enjoy the beauty of the world can be taken away as a result of blameless deeds. This unfortunate fate befell a 13 year old girl who was sexually abused by her stepfather. As a result, his life changed completely and his passion was no longer visible, due to the injuries he had suffered both physically and psychologically. In this study, the aim of this research is to look at the medicolegal aspect in cases of sexual abuse of children by their stepfather. In addition, he also wants to see law enforcement that can happen to his stepfather due to sexual harassment. The method used in this research is literature with descriptive research type. The results of this study are that in the medicolegal aspect, a visum et repertum will be carried out to strengthen evidence of law enforcement on victims. Furthermore, the strong evidence will continue to the law enforcement policies in effect in Indonesia. Law enforcement in cases of sexual abuse of children aged 13 years by stepfather, has been regulated in the Criminal Code (KUHP) of 1981, namely in article 284 paragraph (1), article 285, article 286, article 287 paragraph (1) , article 288 paragraph (1) and article 294 paragraph (1).